2000
DOI: 10.1136/gut.46.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Replication error phenotype, clinicopathological variables, and patient outcome in Dukes' B stage II (T3,N0,M0) colorectal cancer

Abstract: Aims-To examine the relation between the replication error (RER) phenotype and other genetic events, clinical features, and long term survival in patients with Dukes' B stage II (T3,N0,M0) colorectal cancer. Methods-RER phenotype was investigated in 159 patients by PCR amplification of microsatellite marker loci on chromosomes 5q, 17p, 17q, and 18q from tumour DNA extracted from archival tissue. Data on activating c-Ki-ras mutations were available from a previous study. Immunohistochemical detection of p53 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 35 publications
3
16
0
2
Order By: Relevance
“…Most published studies suggest that MSI ϩ CRC generally has a more favorable outcome, 4,7,10,12,[31][32][33][34][35] although not all reports agree. 37,38 To our knowledge, our study is the first analysis based on a prospective series, and the analysis restricted to stage C only, eliminating the confounding effect of the unequal stage distribution between MSI ϩ and MSI Ϫ populations. 4,9 -12 Furthermore, unlike in earlier studies, we restricted the analysis to patients treated with 5-FU-based adjuvant chemotherapy, because adjuvant therapy has a substantial effect on outcome and needs to be taken into account when assessing prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most published studies suggest that MSI ϩ CRC generally has a more favorable outcome, 4,7,10,12,[31][32][33][34][35] although not all reports agree. 37,38 To our knowledge, our study is the first analysis based on a prospective series, and the analysis restricted to stage C only, eliminating the confounding effect of the unequal stage distribution between MSI ϩ and MSI Ϫ populations. 4,9 -12 Furthermore, unlike in earlier studies, we restricted the analysis to patients treated with 5-FU-based adjuvant chemotherapy, because adjuvant therapy has a substantial effect on outcome and needs to be taken into account when assessing prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, adjuvant therapy had not been randomized and the stage distribution of MSI ϩ cases was more favorable. Curran et al 38 studied 159 stage B CRC patients, and found no association between survival and MSI status. In a retrospective series of 213 patients with stage C CRC who had not received adjuvant chemotherapy, MSI ϩ cases were found to have a more favorable prognosis.…”
mentioning
confidence: 99%
“…Several studies have found no correlation between MSI and age in patients with colon carcinoma. 17,[27][28][29][30] However, most of those studies had a small sample sizes and may have lacked the power to detect statistically significant associations. hMLH1 expression loss spread over different age groups was not examined systematically in any of those studies.…”
Section: Hmlh1 Expression Loss Age and Gendermentioning
confidence: 99%
“…Furthermore, patients with MSI-H tumours and a high content of activated cytotoxic lymphocytes showed improved overall survival (Guidoboni et al, 2001). Some studies have reported improved survival among colorectal cancer patients with microsatellite unstable tumours (Lothe et al, 1993;Thibodeau et al, 1993;Bubb et al, 1996;Lukish et al, 1998;Halling et al, 1999;Johannsdottir et al, 1999;Massa et al, 1999;Elsaleh et al, 2000;Gryfe et al, 2000;Hemminki et al, 2000;Wright et al, 2000;Ward et al, 2001;Watanabe et al, 2001), while others have not (Messerini et al, 1997;Senba et al, 1998;Feeley et al, 1999;Salahshor et al, 1999;Curran et al, 2000).…”
mentioning
confidence: 99%